Odpowiedzi

2010-03-13T14:41:09+01:00
A) 6x-24-2= 6x-26
b) 2x+1-3x+3= -x+4
c) -3y+6+4y+8=y+14
d) 5x-5y-5-4x-8=x-5y-13
e) 6a+b-2a+2b=4a+3b
f) 2x-2-2x=-2
g) x(do potęgi2)-x-3x(do potęgi 2) +3x= -2x(do potęgi2)+2x
h) 5a(do p.2) -15a-3a(do 2) +15a = 2a(do 2)
i) 3x(do 2) +xy-xy-y=3x(do 2)-y
22 2 22
Najlepsza Odpowiedź!
2010-03-13T14:41:32+01:00
A) 6(x - 4)- 2= 6x - 24 -2 = 6x -26
b) 2(x + 1)- 3(x - 1)= 2x +2 -3x+ 3= -x+5
c)-3(y - 2) + 4(y +2)= -3y+ 6 +4y +8= y+ 14
d) 5(x - y - 1)- 4(x + 2)= 5x - 5y- 5 - 4x - 8 =-x - 5y -5
e) 2(3a + b) - 2(a - b)= 6a+ 2b - 2a+ 2b= 4a + 4b
f) ½(4x - 4) - 2x= 2x - 2 - 2x= -2
g) x(x - 1) - 3(x² - x)= x² - x - 3x² -3x = -2x² - 4x
h)5a(a - 3)- 3a(a - 5)= 5a² - 15a - 3a² + 15a= 2a²
i) 3x(x +⅓y) -2y (½x...

dokończ przykład ,,i,, to i jego zrobie
27 3 27
  • Użytkownik Zadane
2010-03-13T14:46:40+01:00
A) 6(x - 4)- 2=6x-24-2=6x-26
b) 2(x + 1)- 3(x - 1)=2x+2-3x+3=-x+5
c)-3(y - 2) + 4(y +2)=-3y+6+4y+8=y+14
d) 5(x - y - 1)- 4(x + 2)=5x-5y-5-4x-8=x-5y-13
e) 2(3a + b) - 2(a - b)=6a+2b-2a+2b=4a+4b
f) ½(4x - 4) - 2x=2x-2-2x=-2
g) x(x - 1) - 3(x² - x)=x²-x-3x²+3x=-2x²+2x
h)5a(a - 3)- 3a(a - 5)=5a²-15a-3a²+15a=2a²
i) 3x(x +⅓y) -2y (½x -½)=` 3x²+xy-xy+y=3x²+y
17 4 17